1977
DOI: 10.3171/jns.1977.46.4.0446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subarachnoid hemorrhage on cerebral blood volume, blood flow, and oxygen utilization in humans

Abstract: Forty-five studies of regional cerebral blood volume (rCBV), regional cerebral blood flow (rCBF), and regional cerebral oxygen utilization (rCMRO2) were performed in 30 patients undergoing diagnostic cerebral angiography for evaluation of a subarachnoid hemorrhage due to a ruptured intracranial aneurysm. Tracer methods employing radioactive oxygen-15 were used to measure rCBV, rCBF, and rCMRO2. The patient studies were divided into groups based on their neurological status and the presence or absence of cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
2
8

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(117 citation statements)
references
References 28 publications
5
102
2
8
Order By: Relevance
“…This is enabled by a prolonged MTT since the slow flow of blood results in greater extraction of oxygen. [16] In the present study, patients were scanned on admission in the subacute phase after SAH. Clinically stable patients had initially highest global brain CBF values compared to patients with clinical deterioration and showed an increasing CBV, which represents adequate autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…This is enabled by a prolonged MTT since the slow flow of blood results in greater extraction of oxygen. [16] In the present study, patients were scanned on admission in the subacute phase after SAH. Clinically stable patients had initially highest global brain CBF values compared to patients with clinical deterioration and showed an increasing CBV, which represents adequate autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] reported that there was a risk of postoperative neurological deficit in patients with impaired autoregulation. 6 Several intravenous drugs such as trimethaphan (TMP), nitroglycerine (TNG), adenosine and sodium nitroprusside (SNP) have been used to induce hypotension but it is difficult to identify a preferable drug.…”
Section: Nous Avons Dtudid La Rdactivitd Vasomotrice Cdrdbrale Au Co mentioning
confidence: 99%
“…Voldby et al found a concomitant decrease of CMRO 2 with arterial caliber, indicating secondary metabolic impairment due to cerebral vasospasm (Voldby et al, 1985). Other authors did not observe an additional depression of CMRO 2 with the appearance of delayed vasospasm and advocated a primary reduction of metabolism by SAH (Grubb et al, 1977;Carpenter et al, 1991;Frykholm et al, 2004). All of these studies, however, measured CBF and metabolic parameters in patients at various times after SAH and after hospital admission.…”
Section: Introductionmentioning
confidence: 98%